Penerapan Augmented Reality (AR) Berbasis Proyek sebagai Inovasi Pembelajaran Bahasa Inggris Interaktif untuk Siswa SMA - Syafari, Nofiana; Sagita, Mustakim; Zulfarazi; Sagita, Eva Sulastri; Devi, Diana; Amelia, Fitri (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2026)
This community service article addresses the need for innovative and engaging English language learning methods for high school students (SMA). The shift in educational paradigms requires educators to integrate technology that supports interactive and experiential learning. This program focuses on the implementation of Project-Based Learning (PBL) integrated with Augmented Reality (AR) technology to stimulate students' interest and enhance their English proficiency. The AR approach allows students to create digital objects (such as 3D models or interactive videos) anchored to real-world triggers, turning abstract language concepts into concrete, tangible, and fun experiences. The method involved three main stages: teacher training on AR content creation tools, student workshops on developing English-based AR projects (e.g., creating an AR tour guide for the school or an interactive vocabulary quiz), and the final implementation/exhibition of the AR projects. The results demonstrated a significant positive impact on students' motivation, collaborative skills, and practical language competence, especially in speaking and vocabulary mastery. AR successfully served as a supporting factor to create a wide and conducive learning environment. This project confirms that integrating emerging technologies like AR through a project-based approach is an effective and comprehensive strategy to optimize the potential and holistic growth of SMA students in English learning.